Influências do controle de nível e transparência da água impostos pela formação do reservatório de Porto Primavera sobre peixes de diferentes categorias tróficas do alto rio Paraná. - Abujanra, Fabiane (2007)
In the Paraná River basin, similar to what is happening in many others around the world, the systems "River-floodplain" have been changed so important for regulating the flow imposed by impoundments upstream, affecting the intensity, the duration and timing of flooding and, in consequence, the availability of food. Among other impacts that promote downstream reservoirs, stand out those related to retention of the material in suspension, increasing its erosive capacity and increasing the water transparency, and this effect is amplified in rivers that have reservoir cascade. In light of these changes, this thesis aims to assess the effects of reservoirs built upstream from the floodplain of the Upper Paraná River, in view of the importance of integrity in the areas of flooded plains in the maintenance of biological diversity. So in Chapter I, we tried to ascertain whether the inter-annual variations in the attributes of floods (duration, timing, intensity and variability) affect nutritional status of fish, according to the trophic category. That chapter was based on the fact of the flood pulse of changing the composition, quantity and quality of food resources available to fish and that the effluent water from dams has changed its characteristics in relation to the processes of transportation and sedimentation. In Chapter II, we have evaluated the temporal variation in the water transparency in environments with different degrees of influence in the Porto Primavera Reservoir, considering periods before and after its formation, in order to relate this variation with the abundance of a non-native visual fish-predator (Cichla kelberi).